OPERATIONS NECESSARY FOR THE DIAGNOSIS ANALYSIS OF THE ORGANIZATION - CAIUS LĂZĂRESCU (Annals of the University of Petrosani: Economics)
The diagnosis analysis is as important as is necessary for any profit or non-profit organization, it shows the situation of the organization, helps to prevent the risks, threats and future forecast. The diagnosis analysis must present: the general situation, financial situation, human and managerial potential, technical and technological potential of the organization. Once known these aspects important for the organization, the decision or decisions can be made being aware of it and in real time. The diagnosis analysis is a procedure which is achieved in a relatively short period of time and offers solutions with global character, formulates an action program which will include detailed analysis. The high degree of complexity of the analysis needs a multidisciplinary training which can establish the method, to collect and process the data and to offer the solutions, for which this can be made by specialized companies or by specialized staff from organization self-analysis.